Inhibition kinetics of acetosyringone on xylanase in hydrolysis of hemicellulose. Issue 9 (1st September 2020) - Liu, Feng; Xu, Wen-Fei; Mu, Hang; Lv, Zhi-Rong; Peng, Jie; Guo, Chao; Zhou, Hai-Meng; Ye, Zhuo-Ming; Li, Xu-Hui
ABSTRACT: Many phenolic compounds, derived from lignin during the pretreatment of lignocellulosic biomass, could obviously inhibit the activity of cellulolytic and hemicellulolytic enzymes. Acetosyringone (AS) is one of the phenolic compounds produced from lignin degradation. In this study, we investigated the inhibitory effects of AS on xylanase activity through kinetic experiments. The results showed that AS could obviously inhibit the activity of xylanase in a reversible and noncompetitive binding manner (up to 50% activity loss). Inhibitory kinetics and constants of xylanase on AS were conducted by the HCH-1 model ( β  = 0.0090 ± 0.0009 mM −1 ). Furthermore, intrinsic and 8-anilino-1-naphthalenesulfonic (ANS)-binding fluorescence results showed that the tertiary structure of AS-mediated xylanase was altered. These findings provide new insights into the role of AS in xylanase activity. Our results also suggest that AS was an inhibitor of xylanase and targeting AS was a potential strategy to increase xylose production. Graphical abstract: Acetosyringone inhibited xylanase activity in a reversible and non-competitive binding manner, which might be related to the disruption of tertiary structure of xylanase.